Visual Acuity Improvement of Cataract Patients After Cataract Surgery at Sumbawa Hospital in 2018 - Siska Takarai; I Wayan Gede Jayanegara; Anak Agung Mas Putrawati Triningrat; Ni Made Ari Suryathi; Ariesanti Tri Handayani; Anak Agung Ayu Sukartini Djelantik; Angelo Doniho; Anthea Casey; Giovani Faustine (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
A cataract is the most common cause of vision impairment and blindness worldwide. The Rapid Assessment of Avoidable Blindness survey held in 2014 - 2016 showed that the prevalence of blindness in West Nusa Tenggara was the second highest in Indonesia. This prevalence was expected to be higher in rural areas due to cultural barriers, patient education, and accessibility to eye-care facilities. This study aims to evaluate visual acuity improvement after cataract surgery and observe the sight restoration rate. The participants of this study were cataract patients who underwent surgery at Sumbawa Hospital West Nusa Tenggara between 27 - 30 August 2018 in a social service program held by the Sanglah General Hospital team. Surgery was not performed on patients who did not desire surgery, in cases where the surgery would not improve visual function, and on patients who were known to be medically unfit for safe surgical intervention. Demographic data and visual acuity at admission and postoperative day one were recorded and analyzed. The output of this program was qualitatively measured by analyzing the SRR. A total of 86 patients were included in this study. Visual acuity postoperative day one showed improvement, and the blindness percentage dropped to 51.16%. The sight restoration rate observed in this study was 58.14%. Although the benefits of cost-effective cataract surgery are straightforward, challenges to executing the procedure remain high, such as unaffordability surgery costs and accessibility to eye-care facilities and infrastructures. Equitable growth in other fields can automatically increase healthcare services in rural areas and encourage healthcare workers to spread evenly.